Two antibacterial spiro compounds from the roots of Artemisia pallens wall: evidence from molecular docking - Honmore, Varsha S.; Natu, Arun D.; Khedkar, Vijay M.; Arkile, Manisha A.; Sarkar, Dhiman; Rojatkar, Supada R. (Natural Product Research, 2022)
Bioassay-guided isolation from acetone extract of the roots of Artemisia pallens Wall yielded two spiro compounds (1 and 2). The structures of these compounds were determined on the basis of spectroscopic techniques such as IR, MS, 1 D and 2 D- NMR. The acetone extract, fractions and the isolated two compounds were investigated for their antibacterial activity against two gram negative (E. coli, P. aeruginosa) and two gram positive (S. aureus, B. subtilis) bacterial strains. Compound (2) showed the best spectra of activity with IC50 and MIC values between 2.48-3.08 and 12.78 - 21.77 mu M and Compound (1) with 2.57-3.69 and 38.17 - 80.57 mu M, respectively, for the four bacterial strains, whereas inactive against Mycobacterium tuberculosis. Molecular docking study could further help in understanding the various interactions between these compounds and DNA gyrase active site in detail and thereby could provide valuable insight into the mechanism of action.
Keywords: antibacterial activity; antimycobacterial activity; Artemisia pallens; Asteraceae; Molecular docking; spiro compound